Phosphorylated Hsp27 is mutually exclusive with ATRX loss and the IDH1R132H mutation and may predict better prognosis among glioblastomas without the IDH1 mutation and ATRX loss. Issue 8 (17th March 2018) - Cai, Hong-Qing; Wang, Peng-Fei; Zhang, Hai-Peng; Cheng, Zhi-Jian; Li, Shou-Wei; He, Jie; Zhang, Yu; Hao, Jia-Jie; Wang, Ming-Rong; Yan, Chang-Xiang; Wan, Jing-Hai
Abstract : Aim: To identify biomarkers for accurate classification of glioma. Patients and methods: We evaluated the heat shock protein 27 (Hsp27), phosphorylated Hsp27 (p-Hsp27), ATRX and IDH1 R132H proteins using immunohistochemistry in 421 glioma tissues. The χ 2 test was used to assess the relationship between molecular alterations and clinico-pathological parameters. Kaplan-Meier survival curves were constructed, and differences were detected by the log-rank test. Results: We found that Hsp27 and p-Hsp27 were mainly expressed in aggressive astrocytic gliomas. However, neither Hsp27 nor p-Hsp27 expression was related to survival time for any grade of glioma. Interestingly, p-Hsp27 was mutually exclusive with ATRX loss (ATRX − ) and the IDH1 R132H mutation, except for one case of anaplastic astrocytoma. We classified glioblastomas (GBMs) into three subtypes: ATRX − /IDH1 R132H, high p-Hsp27 expression (p-Hsp27 + ) and none of these three markers. ATRX - /IDH1 R132H showed the longest median survival (19.6 months). The prognostic difference between p-Hsp27 + and none of these three markers was significant (15.0 vs 13.1 months, P=0.045). Moreover, p-Hsp27 + predicted better sensitivity for standard therapy among GBMs without the IDH1 mutation and ATRX loss (26.3 vs 15.5 months, P=0.008). Conclusion: p-Hsp27 is a novel biomarker of glioma and might have important clinical value for further classification of patients with wild-type IDH1 and normal ATRX expression, for evaluating prognosis and for guidance for adjuvant therapy.